(untitled) (Research, Society and Development, 2020)
The present study aimed to investigate the presence of Toxoplasma gondii in urine and saliva samples collected from experimentally infected cats, an unprecedented fact in consulted literature. Six felines, males, serologically negative (IgG) for T. gondii were selected and divided into two experimental groups. Four cats were inoculated with 2x105 tachyzoites (RH strain) (Group I), and two cats were kept as control group (Group II). Before inoculation (days -7 and 0) and on the 7th, 14th, 21th, 28th, 42th, 56th and 70th post inoculation days (PID), all animals were anesthetized with tiletamine hydrochloride and zolazepam (dosage of 15 mg/Kg) for sampling of urine, saliva and blood. Detection of serological titers was performed by indirect immunoﬂuorescence (IIF) and the detection of the protozoan in the bloodstream of cats (parasitemia) was performed by mouse bioassay. The detection of T. gondii in urine and saliva samples was performed using nested PCR and mouse bioassay. All cats inoculated with T. gondii (GI) seroconverted, different from felines of the GII (control), which remained negative throughout the study. T. gondii parasitemia was diagnosed in all cats in group I, totaling five events between the 7th and 42nd PID. It was not possible to detect T. gondii in urine and saliva from infected and control group with nested PCR or mouse bioassay. It was observed that felines experimentally infected with tachyzoites of the strain RH (isolate I) of T. gondii, may not eliminate infectious forms of the parasite through urine and saliva.